One to many QKD network system using polarization-wavelength division multiplexing - Woo, Min Ki; Park, Byung Kwon; Kim, Yong Su; Cho, Young Wook; Jung, Hojoong; Lim, Hyang Tag; Kim, Sangin; Moon, Sung; Han, Sang Wook (IEEE Access, 2020)
The quantum key distribution (QKD) research, which is drawing attention as the next secure communication, is actively expanding from point to point system to network architecture. In QKD network system, it is important to increase the number of users who can securely communicate. Up to date, a wavelength division multiplexing (WDM) architecture has successfully expanded the number of channels without significant system loss, but there is a limitation of increasing channels considering the range of telecommunication wavelength and crosstalk noise, etc. In this article, we propose a polarizing division method that increases user channels independently of wavelengths. The proposed architecture can increase the number of wavelength multiplexed channels by a multiple of the polarization number. We identify the issues in the QKD network system that may occur when using polarization and wavelengths simultaneously, then provide solutions and optimize the system operation accordingly. Finally, we describe a field test result of a one to many QKD network system that shows successful key exchange with 3% QBER.
Keywords: Crosstalk noise; Key exchange; Network systems; Point to point; Proposed architectures; System loss; System operation; Telecommunication wavelengths; Polarization division multiplexing; Quantum cryptography; Quantum key distribution network